Studies on Schismatoglottideae (Araceae) of Borneo XVII: The Schismatoglottis Hottae Complex, a new informal taxon, and three new species from Sarawak, Malaysian Borneo - Wong, Sin Yeng; Boyce, P.C; S.L., Low (Singapore Botanic Garden's, 2012)
On the basis of a suite of shared morphological characters, the Schismatoglottis Hottae Complex is defined as a Borneo-endemic informal taxon in the Schismatoglottis Asperata Group. Four species, three novel, are assigned to the Hottae Complex: S. hottae Bogner & Nicolson, S. dilecta S.Y. Wong, P.C.Boyce & S.L. Low, sp. nov., S. mira S.Y. Wong, P.C. Boyce & S.L. Low, sp. nov., and S. thelephora S.Y. Wong, P.C. Boyce & S.L. Low, sp. nov. A key to species of the Hottae Complex is proffered. Schismatoglottis hottae is illustrated from the Holotype herbarium material, the three novelties from living plants.